Trade-offs encountered in traditional mobility enhancement techniques applied to contact-controlled thin film transistors - Roshna B. Raj; Ashutosh Kumar Tripathi; Shiny Nair; T. Mukundan; T. K. Shahana (Journal of Information Display)
Various mobility enhancement strategies are used at the material, process, and design geometry levels, to improve the performance of conventional thin film transistors (TFTs). These include the optimization of contact barrier height, semiconductor carrier concentration, post-annealing, and channel length optimization. In this study, the effects of these strategies on the performance metrics of contact-controlled amorphous Indium Gallium Zinc oxide (a-IGZO) TFTs are analyzed. Using a low barrier contact metal and a higher channel concentration can enhance the mobility of these TFTs by aiding the high field mode of operation with barrier lowering effect, but this leads to higher values of saturation coefficient, channel length sensitivity, and saturation voltage, with a lower value of output impedance. For a device working in the low-field mode, though the process of annealing improves the mobility characteristics, it deteriorates contact-controlled performance. Channel length upscaling also negatively affects all the contact-controlled performance metrics except output impedance. Thus, this study brings out the deteriorative effect of conventional mobility enhancement strategies on the performance metrics of a contact-controlled device, by unraveling the underlying semiconductor transport physics and the interplay between contact resistance and channel resistance.